Cryptocurrencies: from characteristics to behaviours - Gonçalves, R.; Pereira, L.; Lopes da Costa, R.; Dias, Á.; Teixeira, N. (International Journal of Applied Systemic Studies, 2022)
Over the past few years, cryptocurrencies have been increasingly spoken and have become a global phenomenon known. Their high volatility and lack of regulation makes these investments very risky, and even though these coins are often associated with criminal activities, an increase on the number of investors is visible every day. Most of the published studies explain the technology behind cryptocurrencies, however, there was no published study that aims to understand what kind of profile these investors have and what are their motivations or expectations. Based on a questionnaires and interviews presented to the investors, this study concluded that there are two separate investor profiles and also understood what are their motivations and expectations for the future. It was also possible to see what vision regulators, private equities and corporate banking have for this new type of currency and if they consider them as a valid mean of payment.